Asuhan Kebidanan Intra Natal Care dengan Kasus Inersia Uteri di Rumah Sakit Umum Dewi Sartika Kota Kendari Tahun 2022 - Suhartati; Esse Tendry Nelly; Arbiyah (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat (LPPM), Institut Teknologi Dan Kesehatan (ITK) Avicenna, 2022)
Background: Uterus inertia is a his with intensity that is less frequent than normal his. Uterus inertia is not a direct cause of maternal death but can be fatal if not handled properly. In 2019, there were 352 deliveries at Dewi Sartika Hospital, Kendari City, 21 of which were accompanied by uterine inertia. Objective: This study aims to study the pattern of midwifery care for mothers with uterus inertia. Methods: Observation of midwifery care management interviews 7 steps verney and SOAP (subjective, objective, assessment, plan). The subject of care is Mrs